Inhibition of SIRT3 by a specific inhibitor induces cellular senescence and growth arrest of ovarian granulosa cell tumor via p53 and NF-κB axis - Ma, Jingxin; Lin, Sailing; Zeng, Chuimian; Wu, Wenhao; Zhang, Qi; Zhu, Guli; Zhang, Qi; Fang, Qiongfang; Fan, Lijun; Takeda, Shunichi; Li, Xiaoyu; Li, Xiushen; et al. (Frontiers in Pharmacology, 2025)
ObjectivesOvarian granulosa cell tumors (GCTs) are rare ovarian malignancies with limited therapeutic options, particularly in advanced stages. SIRT3, an NAD + -dependent deacetylase, is upregulated in GCTs and implicated in tumorigenesis, yet its functional role and underlying mechanisms remain poorly understood. This study aims to investigate the therapeutic efficacy of a novel SIRT3-specific inhibitor, 77-39, in GCTs by targeting SIRT3 and to elucidate the molecular mechanisms underlying its effects.MethodsThis study investigated the effects of a SIRT3-specific inhibitor, 77-39, on GCT cell growth and explored its underlying mechanisms. Using human GCT cell lines KGN and COV434, we assessed the impact of 77–39 on cell viability and proliferation. RNA sequencing and gene set enrichment analyses were performed to elucidate the pathways affected by 77–39. Western blot assays were used to confirm the activation of specific signaling pathways. Additionally, SIRT3 was silenced or overexpressed to observe the corresponding effects on GCT cells. In vivo studies were conducted using xenograft tumor models to evaluate the efficacy and toxicity of 77–39 compared to cisplatin.ResultsWe demonstrated that 77–39 significantly suppressed cell viability and proliferation while inducing cellular senescence in human GCT cell lines KGN and COV434. RNA sequencing and gene set enrichment analyses revealed that 77–39 led to the activation of the p53 and NF-κB signaling pathways, which were confirmed by Western blot assay. Silencing SIRT3 recapitulated the effects of 77–39, while SIRT3 overexpression reversed these effects. Inhibition of p53 or NF-κB rescued GCT cells from 77-39-induced growth arrest and senescence. In vivo studies using xenograft tumor models showed that 77-39 effectively inhibited tumor growth without significant toxicity, contrasting with the higher toxicity of cisplatin.ConclusionThese findings suggest that 77–39 may serve as a novel therapeutic agent for GCTs by targeting SIRT3 and modulating the p53 and NF-κB pathways.